TANGGUNG JAWAB PPAT TERHADAP AKTA YANG TELAH DIBUATNYA (Studi Kasus Putusan Pengadilan Negeri Banjarmasin Nomor 07/PDT.G/1997/PN.BJM) TANGGAL 28 MARET 1997 - , Miming Yuliati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study entitles The Responsibility of the Land Deed Official (PPAT) on the Land Deed Made (A Case Study of the Verdict of State Court Banjarmasin No. 07/PDT.G/ PN.BJM) Dated on March 28, 1997. The purposes of the study are to find out the responsibility of the Land Deed Official (PPAT) on the land deed that was made and canceled by the verdict of the State Court and to find out the legal protection provided for PPAT in performing the official tasks. The study was conducted using a normative juridical method categorized as a doctrinal legal writting. It was based on literature research of legal principles, legal rules, and the systematics of law. In the study, there were two types of data, i.e. primary and secondary data. The primary data were obtained from literature study, while secondary data were obtained from field interview. The former was done by a documentary study, while the latter was done through semi-structured interview. The data collected were analyzed by a qualitative technique. Based on the results of the study, it can be concluded that the Land Deed Official (PPAT) has no responsibility over anything in the cancelation of the land deed made. However, it had moral burden due to the land deed made, because the underlying factors of the cancelation was the bad will of befendant to the Land Deed Official (PPAT) so there was a party that felt to be harmed. The Land Deed Official (PPAT) should have the responsivility both personal and administrative level if it was proven to do any mistakes or ignorance in making the land deed. In the study, the Land Deed Official was not imposed by personal and administrative sanctions or criminal sanction because the mistakes in the making of the land deed official was from the applicant to be made the land deed. Meanwhile, in providing the legal protection for the Land Deed Official in the implementation of their daily tasks, the engagement of building and supervision by IPPAT, the Head of Territorial Office, and the Head of Land Office is very necessary to minimize any mistakes that can likely occur in the making of land deed.